2020
DOI: 10.1038/s41467-020-19539-6
|View full text |Cite
|
Sign up to set email alerts
|

Scalable continuous evolution for the generation of diverse enzyme variants encompassing promiscuous activities

Abstract: Enzyme orthologs sharing identical primary functions can have different promiscuous activities. While it is possible to mine this natural diversity to obtain useful biocatalysts, generating comparably rich ortholog diversity is difficult, as it is the product of deep evolutionary processes occurring in a multitude of separate species and populations. Here, we take a first step in recapitulating the depth and scale of natural ortholog evolution on laboratory timescales. Using a continuous directed evolution pla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 46 publications
4
88
0
Order By: Relevance
“…Ultimately, this could expand both the robustness and catalytic activity of further evolved PCA decarboxylases, but also increase the relatively low number of mutations observed per evolved PCA decarboxylase variant. Furthermore, toggled selection regimes of neutral drifting interrupted by selection (Rix et al, 2020;Zhong et al, 2020), may also increase the hit-rate of the continuous evolution, and limit the false-discovery rate observed in this study (>9/22, >0.45)(Figure 3).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Ultimately, this could expand both the robustness and catalytic activity of further evolved PCA decarboxylases, but also increase the relatively low number of mutations observed per evolved PCA decarboxylase variant. Furthermore, toggled selection regimes of neutral drifting interrupted by selection (Rix et al, 2020;Zhong et al, 2020), may also increase the hit-rate of the continuous evolution, and limit the false-discovery rate observed in this study (>9/22, >0.45)(Figure 3).…”
Section: Discussionmentioning
confidence: 84%
“…With orthogonal in vivo evolution machineries at hand, any trait that can be coupled to growth (e.g. antibiotic resistance, tolerance to cultivation conditions, and/or complementation of auxotrophies) enables facile identification of improved target genes without need for direct screening (Esvelt et al, 2011;Ravikumar et al, 2014;García-García et al, 2020;Rix et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For validation of the scoring function, a set of experimental studies on the substrate ranges of various enzymes was extracted from literature manually, [44][45][46][47][48][49][50][51] as well as a study on organic coupling reactions to test the performance of EHreact on organic, non-enzymatic reactions. 52 Each study reported either the yield or activity of an enzyme/catalyst on a specified substrate under reaction conditions consistent throughout each study.…”
Section: E Data Preparationmentioning
confidence: 99%
“…Nine recent datasets from literature were chosen toward this aim, for which both reactants and products were known (opposed to the more prevalent manner of only reporting reactants). Eight studies comprised enzymatic transformations, reporting the activity of different nitrilases, 44 aminedehydrogenases, 45 alcoholdehydrogenases, 46 carboxyl-methyltransferases, 47 transaminases, 48 tryptophansynthases, 49 amidinotransferases 50 and dehalogenases 51 on diverse sets of substrates. An additional study on seven organic C(sp 2 )-C(sp 3 ) couplings 52 was utilized to showcase the performance of EHreact on non-enzymatic transformations.…”
Section: Validation On Experimental Datamentioning
confidence: 99%
“…This highlights the value of experimental parallelizability available to AHEAD: through evolution experiments that kept each parent clone’s lineages separate, early high achievers such as RBD6 could not outcompete the initially low performing lineages that ultimately gave rise to the most potent neutralizers. This is akin to ‘demes’ in natural evolution, which act to reduce clonal interference and increase overall functional diversity ( 25, 26 ) Indeed, AHEAD’s ability to maximize diversity of high-affinity clones through independent experiments should be valuable in all antibody generation campaigns, given that antibody performance depends on secondary features beyond affinity alone.…”
Section: Main Textmentioning
confidence: 99%